Heaven and hell in medieval Italian art - Barclay Lloyd, Joan (Spunti e Ricerche, 2016)
Images of heaven and hell appear frequently in medieval Italian art. This article will concentrate on some examples in monumental works of fresco and mosaic, which were made before Dante wrote La Divina Commedia, and not on those later creations which show the influence of his poetry on visual art. The poet may not have seen the actual works discussed here, but these artistic representations serve to illustrate the vision Dante and his contemporaries probably had of heaven and hell.